Real Option Financing Under Asymmetric Information - Bouvard, Matthieu (Review of Financial Studies, 2014)
This study examines the financing of innovation in the presence of adverse selection in the capital market. An entrepreneur with private information needs outside funding for a project requiring costly experimentation. Equilibrium contracts use the duration of the experimentation period, together with pay-for-performance, to signal information to outside investors. As a result, investment is delayed, entrepreneurs with stronger growth options receive vested stock options, and entrepreneurs with a lower probability of success are compensated in case of failure. These predictions are in line with empirical evidence on venture capital contracts, and on the impact of internal financing on risk taking. The Author 2012. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.